2009
DOI: 10.3171/2009.3.spine08927
|View full text |Cite
|
Sign up to set email alerts
|

Vertical mobile and reducible atlantoaxial dislocation

Abstract: Object The authors' experience with treatment of 8 patients with “vertical mobile and reducible” atlantoaxial dislocation is reviewed. The probable pathogenesis, radiological and clinical features, and management issues in such cases are discussed. Methods Between January 2006 and March 2008, 8 patients who presented with vertical mobile and reducible atlantoaxial dislocations were treated at the Departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 12 publications
0
39
0
1
Order By: Relevance
“…There was evidence of vertical, mobile, and partially or completely reducible atlantoaxial dislocation (as described by us earlier in 2009) in 18 cases. 23 In patients having basilar invagination, there was occipitalization of the atlas in 33 cases and C2-3 fusion in 4 cases. Radiological images and operative observations revealed that the atlantoaxial joint was "open," functional, and unstable in all patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was evidence of vertical, mobile, and partially or completely reducible atlantoaxial dislocation (as described by us earlier in 2009) in 18 cases. 23 In patients having basilar invagination, there was occipitalization of the atlas in 33 cases and C2-3 fusion in 4 cases. Radiological images and operative observations revealed that the atlantoaxial joint was "open," functional, and unstable in all patients.…”
Section: Resultsmentioning
confidence: 99%
“…23 In several of these cases, the vertical dislocation was subtle but definite. Identification of such vertical dislocation seems to be an important additional parameter suggesting instability of the region and incompetence of the joints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,13 Our experience in dealing with and manually handling unstable atlantoaxial and subaxial spinal facets is more than 25 years long. [1][2][3][4][5][6][7]10,[15][16][17][18][19][20][22][23][24][25][26][27][28][29][31][32][33][34][35][36] We have treated over 1300 cases by atlantoaxial fixation. 22,26 Because of this unique opportunity, we are able to identify the presence or absence of instability rather easily by assessing the local stability situation during an operation by manual bone handling.…”
Section: Responsementioning
confidence: 99%
“…1 In most cases, the adoption of short posterior vertebral fixation techniques 2 (C1-C2) has replaced long occipital-cervical fixation (sub-axial) with good clinical outcomes and the preservation, in large part, of cervical mobility, although with an increased risk of neuro-vascular lesions, particularly of the vertebral artery. The need to extend the fixation to the occipital bone, which may increase the stability of the fixation and improve the clinical outcome, has also been questioned in pure atlantoaxial instabilities.…”
Section: Introductionmentioning
confidence: 99%